2020
DOI: 10.3390/app10134597
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Plant Extracts and Phytochemicals Against Foodborne Pathogens

Abstract: Foodborne diseases are one of the major causes of morbidity and mortality, especially in low-income countries with poor sanitation and inadequate healthcare facilities. The foremost bacterial pathogens responsible for global outbreaks include Salmonella species, Campylobacter jejuni, Escherichia coli, Shigella sp., Vibrio, Listeria monocytogenes and Clostridium botulinum. Among the viral and parasitic pathogens, norovirus, hepatitis A virus, Giardia lamblia, Trichinella spiralis, Toxoplasma and Entamoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 255 publications
0
34
0
Order By: Relevance
“…The incidence of systemic microbial infections such as septicemia, urinary tract infections, meningitis, pneumonia, and gastritis affects the entire human body and contributes significantly to global mortality. Food-borne diseases are mostly caused by pathogens including Staphylococcus , Shigella , Salmonella , Bacillus , Escherichia coli , Clostridium , and Pseudomonas [ 69 ]. Plant-derived bioactive compounds are promising sources of antimicrobials.…”
Section: Biological Activities Of Guava Leaf Extractsmentioning
confidence: 99%
“…The incidence of systemic microbial infections such as septicemia, urinary tract infections, meningitis, pneumonia, and gastritis affects the entire human body and contributes significantly to global mortality. Food-borne diseases are mostly caused by pathogens including Staphylococcus , Shigella , Salmonella , Bacillus , Escherichia coli , Clostridium , and Pseudomonas [ 69 ]. Plant-derived bioactive compounds are promising sources of antimicrobials.…”
Section: Biological Activities Of Guava Leaf Extractsmentioning
confidence: 99%
“…Herbal extracts have been known to be effective against parasites, such as Plasmodium spp. [34], Schistosoma mansoni [35,36], Toxoplasma gondii [37], and helminths [38]. Allen et al [39] found that dried leaves of Artemisia annua provided significant protection against lesions due to E. tenella infection.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials are the compounds that either kill or inhibit the growth of broad-spectrum bacteria, virus, or fungi. Studies has shown that phytochemicals exert antimicrobial activity via mechanism of action like damage of cell membrane, inhibition of enzyme and toxin activity, suppression of virulence factor or by formation of bacterial biofilm (Guldiken et al 2018, Ullah et al 2020. Several herbs and spices used in Nepali kitchen exhibit highly potent bioactive compounds such as flavonoids, alkaloids, tannins, glycosides, saponins which attributed as a defense mechanism against different microorganisms, insects and herbivores.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%